Biofuels for road transport: Analysing evolving supply chains in Sweden from an energy security perspective - Månsson, A.; Sanches-Pereira, Alessandro; Hermann, S. (ELSEVIER SCI LTD, 2014)
The use of biofuels for road transport in Sweden has increased during the past 10. years as policymakers stimulate demand in response to concerns about climate change. Using a supply chain approach, this paper analyses: (i) existing biofuel supply chains in Sweden (biogas, biodiesel and bioethanol) in terms of security of supply, and (ii) possibilities to achieve synergies between implementation of climate change mitigation practices and security of supply objectives, through increased production and use of biofuels. We argue that synergies can arise when exposure to upstream market risk decreases, the risk of the feedstock does not correlate with the fuel that it replaces, producers can switch between feedstocks and end user vulnerability to disruptions decreases. In the current Swedish context, the features of the biogas supply chain make it the most beneficial option, followed by biodiesel. In the way it has been implemented, bioethanol is the least favourable option. The paper concludes by outlining how biofuels could contribute to security of supply in the future. © 2014 Elsevier Ltd.